Comparative genomic analysis of Escherichia coli isolates from cases of bovine clinical mastitis identifies nine specific pathotype marker genes. Issue 7 (6th July 2021) - Jung, Dongyun; Park, Soyoun; Ruffini, Janina; Dussault, Forest; Dufour, Simon; Ronholm, Jennifer
Abstract : Escherichia coli is a major causative agent of environmental bovine mastitis and this disease causes significant economic losses for the dairy industry. There is still debate in the literature as to whether mammary pathogenic E. coli (MPEC) is indeed a unique E. coli pathotype, or whether this infection is merely an opportunistic infection caused by any E. coli isolate being displaced from the bovine gastrointestinal tract to the environment and, then, into the udder. In this study, we conducted a thorough genomic analysis of 113 novel MPEC isolates from clinical mastitis cases and 100 bovine commensal E. coli isolates. A phylogenomic analysis indicated that MPEC and commensal E. coli isolates formed clades based on common sequence types and O antigens, but did not cluster based on mammary pathogenicity. A comparative genomic analysis of MPEC and commensal isolates led to the identification of nine genes that were part of either the core or the soft-core MPEC genome, but were not found in any bovine commensal isolates. These apparent MPEC marker genes were genes involved with nutrient intake and metabolism [ adeQ, adenine permease; nifJ, pyruvate-flavodoxin oxidoreductase; and yhjX, putative major facilitator superfamily (MFS)-type transporter], included fitness and virulence factors commonly seen in uropathogenic E. coli ( pqqL, zinc metallopeptidase, and fdeC, intimin-like adhesin, respectively), and putative proteins [ yfiE, uncharacterized helix-turn-helix-type transcriptional activator; ygjI, putative inner membrane transporter; and ygjJ, putative periplasmic protein]. Further characterization of these highly conserved MPEC genes may be critical to understanding the pathobiology of MPEC.